The Art Of "Chemistry" By Boborakhim Mashrab - Nilufar Mahamadaliyevna Kayumova (Zien Journals, 2025)
The article examines the work "Alchemy" by Boborahim Mashrab, one of the talented representatives of Uzbek classical literature. The work analyzes his poems of ethical and educational significance in the direction of Sufism.
Keywords: Uzbek classical literature; analysis; art